Metode Doa dalam Pembelajaran - Rusdiono Mukri; Mujahidin, Endin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the implementation of the prayer method in learning and its impact or influence on student learning achievement. The research used descriptive qualitative method which was carried out by collecting data obtained from documentation, observation and interviews, and supported by literature studies, both from books and journals. The results showed that the prayer method is very necessary in learning. However, in its implementation, the prayer method cannot stand alone. The prayer method in learning must be combined or integrated with other methods such as lecture methods, discussions, question and answer, storytelling, exercises (drills), sociodrama, and other methods. The prayer method is proven to make students peace of mind and are motivated to improve their learning achievements. Therefore, this method must be introduced and implemented in learning, both for educational institutions, especially Islamic educational institutions, as well as public schools. In addition, the teacher must plan every lesson, regardless of the method used in learning, both in class and outside the classroom, to guide students to pray, both before the lesson begins and before the lesson ends. Keywords: prayer method; motivation; peace of soul